HUBUNGAN SIKAP CARING PERAWAT DENGAN KEPUASAN KELUARGA PASIEN DI RUANG RAWAT INAP INTENSIF ANAK RUMAH SAKIT SANTOSA BANDUNG CENTRAL - kartini herlita, kevin (Jurnal Kesehatan & Disiplin Ilmu, 2025)
Caring attitude is one of the measures used to analyze health service users. Nurses' caring attitude towards patients can play a role in determining the number of patients who visit the hospital. The purpose of this study was to describe the caring attitude of nurses and family satisfaction of inpatients in the Children's Intensive Room of Santosa Hospital, and to determine the relationship between the caring attitude of nurses and family satisfaction of inpatients in the Children's Intensive Room of Santosa Hospital. The method of data collection in this research is cross sectional method. The results of this study were out of 32 respondents there were 15 people (46.9%) caring nurses were good, and 12 people (37.5%) patient family satisfaction was less. The Kolmogorof-Smirnov test results obtained a p value of 0.002 smaller than 0.05, so there is a relationship between the attitude of caring nurses with the satisfaction of the family of patients hospitalized in the Children's Intensive Room of Santosa Hospital.